2019
DOI: 10.4149/neo_2018_180820n630
|View full text |Cite
|
Sign up to set email alerts
|

Liver kinase B1 suppresses metastasis and angiogenesis of lung cancer: involvement of the Shh signaling pathway

Abstract: Liver kinase B1 (LKB1) has been shown to be involved in many cancers. However, the underlying mechanism remains unclear. This study aimed to reveal the mechanism through which LKB1 performs its role in lung cancer. LKB1 shRNA and overexpression plasmid were employed to investigate the role of LKB1 in lung cancer in vitro and in vivo. The involvement of Shh signaling pathway was assessed by western blot. Silencing LKB1 promoted migration, invasion and angiogenesis of lung cancer cells, while overexpression of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, the mRNA and protein levels of E-Ca were dramatically increased, while the expressions of N-Ca and vimentin were significantly decreased in TPC-1 and BCPAP cells with LKB1 overexpression. For the angiogenesis, LKB1 was also found to suppress lung cancer angiogenesis by Shh signaling pathway [20]. Depletion of LKB1 could accelerate the angiogenesis via VEGF [21].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the mRNA and protein levels of E-Ca were dramatically increased, while the expressions of N-Ca and vimentin were significantly decreased in TPC-1 and BCPAP cells with LKB1 overexpression. For the angiogenesis, LKB1 was also found to suppress lung cancer angiogenesis by Shh signaling pathway [20]. Depletion of LKB1 could accelerate the angiogenesis via VEGF [21].…”
Section: Discussionmentioning
confidence: 98%
“…The silencing of liver kinase B1 (LKB1) increased levels of VEGF, MMP-2 and MMP-9, enhanced HUVEC activity and migration, and promoted angiogenesis ( 59 ). In addition, after LKB1 silencing, mRNA levels of key molecules in the Shh signaling pathway, such as Shh, Ptch, Smo and Gli1, were increased, and nuclear translocation of Gli1 was enhanced, suggesting that LKB1 can inhibit the Shh signaling pathway, thus inhibiting angiogenesis in lung cancer.…”
Section: Novel Angiogenic Regulators In Lung Cancer Treatmentmentioning
confidence: 99%
“…In a 2018 study by Xu, Notch signaling pathway inhibitor DAPT was used to negatively regulate the Notch signaling pathway and downregulate RhoA, RhoC, and MMP9, and upregulate RhoB, thereby inhibiting the metastasis and invasion of NSCLC (91). In addition, in 2019, Zheng et al also found that after the Sonic hedgehog (Shh) signaling pathway was transplanted by LKB1, Shh's role in regulating lung cancer metastasis and angiogenesis was also suppressed (92).…”
Section: Signaling Pathways and Lung Cancer Metastasismentioning
confidence: 99%